A Project study on the Nutritional Division of Wyeth-Suaco Laboratories, Inc. - Aplasca, Morgan R.; Arrieta, Eduardo T. Jr; Castañeda, Romeo P.; Derecho, Arthur D.; Miravalles, Lily Beth M.; Te, Elmer B. (College of Engineering, 1987)
The objective of this paper is to try to apply the knowledge gained from lectures in ?Production Systems? (I.E. 51) and to examine the production system of an actual firm, in this case Wyeth-Suaco Laboratories Inc. The scope of the project study is limited to the departments under the Plant Manager dealing with the manufacture of nutritional products. The principal method of gathering information was interviewing key personnel. These interviews were correlated to the forms collected and the past records available for examination. Obtaining information was rather difficult, and many areas of interest fell under the ?confidential? classification. The data collected was assessed with the aid of organizational charts, process flow charts, and similar techniques. Analysis yielded one main problem: the company was unable to meet the production-inventory requirement. This was caused by: a) limited plant capacity, b) inaccurate forecasting. The solutions formulated are as follows: 1) a determination of the critical equipment of the production line was performed and tested through simulation; 2) the use of forecasting models other than that presently used by WSLU. The recommendations are that the company procures one Pinroda Dryer within 3.47 months from May 1982, and that the forecasting model should be the Double Moving Average. It is felt that had more cost data been available, a more practical and economically relevant recommendation could have been presented.